Mineralogy and geochemistry of atypical reduction spheroids from the Tumblagooda Sandstone, Western Australia - Fox, David C.M.; Spinks, S.C.; Thorne, R.L.; Barham, Milo; Aspandiar, Mehrooz; Armstrong, J.G.T.; Uysal, T.; Timms, Nick; Pearce, M.A.; Verrall, M.; Godel, B.; Whisson, B. (WILEY, 2020)
Reduction spheroids are small-scale, biogenic, redox-controlled, metal enrichments that occur within red beds globally. This study provides the first analysis of the compositionally unique reduction spheroids of the Tumblagooda Sandstone. The work aims to account for their composition and consequently improve existing models for reduction spheroids generally, which presently fail to account for the mineralogy of the Tumblagooda Sandstone reduction spheroids. Interstitial areas between detrital grains contained in the cores of these reduction spheroids are dominated by microplaty haematite, in addition to minor amounts of svanbergite, gorceixite, anatase, uraninite, monazite and illite. The haematite-rich composition, along with an absence of base metal phases and the vanadiferous mica roscoelite, makes these reduction spheroids notable in comparison to other global reduction spheroid occurrences. Analyses of illite crystallinity provide values for samples of the Tumblagooda Sandstone host rock corresponding to heating temperatures of ca 200°C. Consequently, while Tumblagooda Sandstone reduction spheroids formed via the typical metabolic processes of dissimilatory metal-reducing bacteria, the combination of a unique mineralogy and illite crystallinity analysis provides evidence of more complex late-stage heating and reoxidation. This has not previously been recognised in other reduction spheroids and therefore expands the existing model for reduction spheroid genesis by also considering the potential for late-stage alteration. As such, future reduction spheroid studies should consider the potential impact of post-formation modification, particularly where they are to be used as evidence of ancient microbial processes; such as in the search for early evidence of life in the geological record on Earth or other planets. Additionally, because of their potential for modification, reduction spheroids serve as a record of the redox history of red beds and their study could provide insights into the evolution of redox conditions within a given red bed during its diagenesis. Finally, this paper also provides insights into the relatively understudied diagenetic history of the Tumblagooda Sandstone; supplying the first reliable and narrow constraints on its thermal history. This has important implications for the thermal history of the Carnarvon Basin and its petroleum prospectivity more broadly.